In-house 3D-printed aligners: effect of in vivo ageing on mechanical properties. (5th May 2021) - Can, Esad; Panayi, Nearchos; Polychronis, Georgios; Papageorgiou, Spyridon N; Zinelis, Spiros; Eliades, George; Eliades, Theodore
Summary: Objective: To investigate alterations in the mechanical properties of in-house three-dimensional (3D) printed orthodontic aligners after intraoral ageing. Materials and methods: Sixteen 3D-printed aligners (TC-85DAC resin, Graphy, Seoul, Korea) were used for the purpose of the study, which were divided into 10 control (not used) aligners and 6 materials retrieved from 4 patients after 1-week service (retrieved group). Samples from the control group were analysed by attenuated total reflectance-Fourier-transform infrared (ATR-FTIR) spectroscopy. Samples from control/retrieved groups were embedded resin and subjected to instrumented indentation testing (IIT) to record force–indentation depth curves, calculating the following (as per ISO 14577-1, 2002 standard): Martens hardness (HM), indentation modulus ( E IT ), and elastic index ( η IT ), and the indentation relaxation index ( R IT ). Differences between control and retrieved 3D-printed aligners were checked with Mann–Whitney/ t -tests at an alpha = 5%. Results: ATR-FTIR analysis showed that aligners were made of a vinyl ester–urethane material. The results of the IIT testing were: HM (control: median 91.5 N/mm 2, interquartile range [IQR] 88.0–93.0/as-retrieved: median 90.5 N/mm 2, IQR 89.0–93.0); E IT (control, mean 2616.3 MPa, standard deviation [SD] 107.0 MPa/retrieved, mean 2673.2 MPa, SD 149.4 MPa); η IT (control: median 28.6%, IQR 28.2–30.9%/as-retrieved: median 29.0%, IQR 28.7–29.2%); and R IT (control: median 45.5%, IQR 43.0–47.0%/as-retrieved: median 45.1%, IQR 45.0–45.3%). No differences between as-retrieved and control aligners were found for any of the mechanical properties tested ( P > 0.05 in all instances). Conclusion: The mechanical properties of the in-house 3D-printed aligners tested were not affected after 1 week in service period.